Factors affecting the use of fertilizers and manure by smallholders: The case of Vihiga, western Kenya - Waithaka, M.M.; Thornton, Philip K.; Shepherd, Keith D.; Ndiwa, Nicholas N. (Springer, 2007)
Sub-Saharan Africa faces huge food supply challenges due to increasing human population, limited opportunities to increase arable land, and declining yields associated with continuously declining soil fertility. To cater for their food requirements, smallholders use only modest levels of inorganic fertilizers and rely to a large extent on manure, which is generally of low quality. To explore factors influencing fertilizer and manure use at the farm level, 253 farm households in Vihiga district of western Kenya were sampled. A pair of Tobit models was used to relate amounts of manure and fertilizer used to household variables. The results indicate that the use of both manure and fertilizer reciprocally influence each other and are strongly influenced by household factors, and also imply that manure and fertilizer uses are endogenous. Policy changes are required to (1) reduce the burden on farming alone in rural areas; (2) promote the use of higher-cost, higher-value inputs such as fertilizers; (3) improve access to input and output markets; and (4) encourage farmer education so as to promote sustainable soil fertility management. Improved understanding of the biophysical and socioeconomic environment of smallholder systems can help target sustainable soil fertility interventions more appropriately.